Penyuluhan Manajemen Bencana Dan Pertolongan Pertama Pada Kecelakaan (P3K) Bagi Relawan - Serly Sani Mahoklory; Angriawan Angriawan; Endam Apulina Br Sembiring; Haedir Haedir; Dwi Ardyna Octa Sari (Sahabat Sosial: Jurnal Pengabdian Masyarakat, 2026)
Indonesia is a country prone to natural disasters, such as earthquakes, floods, landslides, and fires. These conditions require community preparedness, especially for volunteers, in dealing with emergencies. Volunteers are often the first to arrive at disaster sites, requiring adequate knowledge and skills in disaster management and first aid (P3K). However, many volunteers still lack an optimal understanding and skills in first aid. This Community Service activity aims to improve volunteers' knowledge and preparedness through disaster management and first aid training. Implementation methods include theoretical training, interactive discussions, first aid simulations and practices, and evaluation through pre- and post-tests. The results of the activity indicate a significant increase in volunteers' knowledge and preparedness in dealing with disaster situations and administering first aid. This activity is expected to enhance volunteers' capacity to support disaster management effectively and safely.